2023
DOI: 10.5334/ijic.7022
|View full text |Cite
|
Sign up to set email alerts
|

Improving Multidisciplinary Team Working to Support Integrated Care for People with Frailty Amidst the COVID-19 Pandemic

Abstract: Multidisciplinary team (MDT) working is essential to optimise and integrate services for people who are frail. MDTs require collaboration. Many health and social care professionals have not received formal training in collaborative working. This study investigated MDT training designed to help participants deliver integrated care for frail individuals during the Covid-19 pandemic. Researchers utilised a semi-structured analytical framework to support observations of the training sessions and analyse the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Some studies identified the need for more H&CP disease-specific training alongside training to support self-care (10,32). This highlights the need to explore more opportunities to promote truly integrated care approaches by developing training and care resources with greater involvement from multidisciplinary teams and patients who live with multimorbidity (33,34). This approach can help embed learning and best practice so that patient experience and services can be improved to account for what matters most to service users (33,34).…”
Section: Interpretation and Comparison With Literaturementioning
confidence: 99%
“…Some studies identified the need for more H&CP disease-specific training alongside training to support self-care (10,32). This highlights the need to explore more opportunities to promote truly integrated care approaches by developing training and care resources with greater involvement from multidisciplinary teams and patients who live with multimorbidity (33,34). This approach can help embed learning and best practice so that patient experience and services can be improved to account for what matters most to service users (33,34).…”
Section: Interpretation and Comparison With Literaturementioning
confidence: 99%
“…These challenges can include chronic diseases, mobility issues, mental health conditions, and social isolation, all of which can significantly impact their quality of life (QoL) [31]. Multidisciplinary teams are well equipped to address these diverse needs by integrating medical care with psychological support, rehabilitation services, and social interventions [32]. This comprehensive approach not only helps in managing the complex health issues more effectively but also supports the overall wellbeing of older patients, enhancing their quality of life and promoting independence [33].…”
Section: Introductionmentioning
confidence: 99%